RARE JUVENILE GIANT FIBROADENOMA - Fatih Uygur; Cengizhan Yiğitler (European Journal of Breast Health, 2009)

(untitled)
Juvenile giant fibroadenoma is an uncommon benign breast tumor most frequently seen in adolescence. The lesions are generally unilateral, painless, solitary masses characterized by rapid growth. Herein we report an uncommon case of 22 cm juvenile giant fibroadenoma weighing 2200 grams.